Evaluation of Antimicrobial Activity in Ethanolic Extract of Caralluma indica - Gnanashree, G.; Sirajudeen, P. Mohamed (International Journal of Scientific Research in Biological Sciences, 2018)
In the present study to investigate the antimicrobial activity in Caralluma indica. Antibacterial activity showed about 3.92mm (50µl), 6.11mm (100µl), 8.25mm (150µl) and 10.98mm (Std.) zone against the test organisms of Escherichia coli. 4.08mm (50µl), 6.23mm (100µl), 8.47mm (150µl) and 11.65mm (Std.) zone against the test organisms of Staphylococcus aureus. 2.17mm (50µl), 4.86mm (100µl), 6.13mm (150µl) and 9.46mm (Std.) zone against the test organisms of Bacillus subtilis. 4.85mm (50µl), 7.32mm (100µl), 9.69mm (150µl) and 12.13mm (Std.) zone against the test organisms of Pseudomonas aeruginos. Antifungal activity showed about 1.95mm (50µl), 4.20mm (100µl), 6.10mm (150µl) and 10.42mm (Std.) zone against the test organisms of Candida albicans. 0.90mm (50µl), 2.81mm (100µl), 5.72mm (150µl) and 8.10mm (Std.) zone against the test organisms of Aspergillus flavus. 0.35mm (50µl), 1.10mm (100µl), 3.66mm (150µl) and 7.90mm (Std.) zone against the test organisms of Aspergillus niger.